2004
DOI: 10.1038/sj.bmt.1704418
|View full text |Cite
|
Sign up to set email alerts
|

Mobilized blood cells vs bone marrow harvest: experience compared in 171 donors with particular reference to pain and fatigue

Abstract: Summary:This prospective study compared the donor experience of blood cell (BC) mobilization and leukapheresis (n ¼ 116) with that of bone marrow (BM) harvest (n ¼ 55). Internal jugular catheters were inserted electively in 89% of BC donors. Most (80%) BM donors had a harvest with general anesthesia; 20% had epidural or spinal anesthesia. Pain and fatigue were frequent with both procedures and were compared in responses to questionnaires. A total of 85% of BM donors reported moderate or severe pain compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…The common adverse events related to G-CSF were bone pain (64.9%), myalgia/arthralgia (58.2%), fatigue (44.1%) and headache (33.0%). The incidences were generally comparable to previous reports [2,3,5,[8][9][10][11][12][13][14] (Supplementary table). Although there are some variations between different studies, the differences might be due to the reported symptoms that were subjective and mostly mild in all studies.…”
Section: Discussionsupporting
confidence: 88%
“…The common adverse events related to G-CSF were bone pain (64.9%), myalgia/arthralgia (58.2%), fatigue (44.1%) and headache (33.0%). The incidences were generally comparable to previous reports [2,3,5,[8][9][10][11][12][13][14] (Supplementary table). Although there are some variations between different studies, the differences might be due to the reported symptoms that were subjective and mostly mild in all studies.…”
Section: Discussionsupporting
confidence: 88%
“…1 Since then, cytokine-mobilized PBPCs collected from healthy sibling or unrelated donors are increasingly used as stem-cell source in the allogeneic setting. 2 PBPCs have been shown to be superior to BMderived stem cells during the early post transplant course. 3,4 The high CD34 þ cell yield in PBPC grafts significantly shortens the post transplant aplasia and the need for blood component support, especially platelets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pain lasting more than 7 days was reported by a larger number of marrow donors than by those who underwent blood cell collection. 4 A comparative study reported that the incidence of bone pain was 65.3% in donors receiving lenograstim and 61.9% in those stimulated with filgrastim. 10 A rare but painful acute complication of filgrastim stimulation, seen in patients 11 and healthy donors, 12 is rupture of the spleen.…”
Section: Epidemiology and Causal Factors Of Specific Pain Syndromes Imentioning
confidence: 99%
“…3 Stem cell donors may experience pain from mobilization of haematopoietic stem cells or collection of bone marrow. 4 The major cause of pain in HSCT recipients is a result of injury to mucosal tissues induced by the conditioning regimen. 5 In addition, pain in HSCT recipients may be due to infection, acute and chronic GVHD as well as adverse effects of some of the drugs administered for GVHD prophylaxis.…”
Section: Introductionmentioning
confidence: 99%